Seasonal variations in the quality and freezability of Red Sindhi bull semen - TIWARI, RITESH; MISHRA, G K; SINGH, R B; REHMAN, S U; RATHORA, K S; SAXENA, S K; SIDDIQUI, M U (The Indian Journal of Animal Sciences, 2012)
The aim of present study is to evaluate the variables affecting semen characteristics in Red Sindhi bulls. Semen ejaculates (771) collected from 4 Red Sindhi bulls during various seasons (winter, summer and rainy) of the year were studied. Ejaculate volume (EVOL), sperm concentration (SCON) showed significant effect of seasons. However, initial motility (IM) and post-thaw motility (PTM) did not differ significantly between seasons. Mean values for semen parameters, viz. number of ejaculates per month, EVOL, IM, SCON, PTM, were 16.06, 4.32±0.07 ml, 66.89±0.37 %, 1043.75±16.35 million/ml and 50.11±0.03 %, respectively. Discard (rejection) rate of frozen semen was the highest in summer (7.52%) followed by rainy (5.12%) and lowest in winter (3.98%).